Aflatoxine titles and mycotic charge of feedstuffs in Greece - Ευσταθίου, Λ.; Παπαδόπουλος, Ε.; Οικονομίδου, Ε. (Journal of the Hellenic Veterinary Medical Society, 2019)
Two hundred forty six (246) foodstuffs samples were received mainly from the regional Veterinary Services, to be tested for the causes of pathologic events In animals. Twenty eight samples (28) with 500 PPB of af latoxine B1 were found I.e. 11.3% (Velasco Flurotoxin meter). Per kind of simple foodstuff were found: the titles which are enreqistred on the table I of the text. In the same samples the total number of mycetes found was determined and in many samples high levels were found.